Enhanced Medium Access Control Protocol for Resolving Node Misbehavior in Wireless Networks - Nordin, Noorsalwati (2007)
In this research, two schemes that enhance the existing misbehavior handling strategy are proposed. The first scheme correlates misbehavior with the traffic characteristics generated by the node deviating from the stipulated protocol. It eliminates the stereotyping of deviation by deriving a multi-scale deviation definition ranging from misbehavior to the underestimation of resource allocation. The scale adaptively enables varying types of misbehavior according to resource requirement. From the performance analysis, it was determined that the scheme is successful in differentiating between misbehavior due to selfishness and under-allocation of resource. In addition, the scheme also enables nodes that are allocated with inadequate resource to achieve higher share of throughput as per its requirement. The second proposed scheme further extends the existing misbehavior handling strategy by detecting excessive allocation of resources. This scheme effectively diminishes the wastage of resources by re-distributing them among the rest of the nodes. The allocation of the resources is carried out on a First- Come-First-Serve basis in order maintain fair characteristics of the 802.11 access mechanism. From the analysis, it was found that when this scheme is employed, the presence of nodes that are over-allocated with resources enables the rest of the nodes to increase their throughput share. The performance analysis of the proposed schemes was conducted with the use of a discrete-event simulator. The simulator was specifically developed for wireless networks incorporating the proposed schemes. It simulates a wireless network comprising non-deviating nodes and nodes that deviate from the MAC protocol due to selfishness, under-allocation and over-allocation of resources. The metrics employed to measure the performance of the proposed algorithms are average throughput, fairness index, channel utilization and throughput ratio. From the analysis of the metrics, it is concluded that with the employment of the proposed scheme, if a node deviates from the protocol and it is allocated with inadequate resources, the scheme will adaptively allow the node to gain the resource as per the degree of its resource under-allocation. On the other hand, if it deviates due to over-allocation, the excess resources will be distributed to other nodes, hence, enabling for the increase of overall network throughput.